015 Pathways to work? Insights from a systematic review of the UK's return to work initiatives for disabled and chronically ill people. (16th November 2010) - Clayton, S; Gosling, R; Povall, S; Misso, K; Bambra, C; Whitehead, M
Abstract : Purpose: Employment rates of chronically ill and disabled people in the UK are low (49%) and 2.7 million are on disability-related state benefits. Recent government policy has seen the introduction of a range of measures aimed at integrating them into the labour market. This paper explores what can be learned for future policy from a synthesis of a wide range of evidence evaluating these policies. Method: We conducted a systematic review and evidence synthesis of empirical studies reporting the employment effects and/or factors influencing the effectiveness of national-level interventions aimed at helping people into work who were not employed and were on some form of disability-related benefit. We excluded measures aimed at reducing short-term sickness absence, localised interventions, and those that were not wholly concerned with helping individuals move into the open labour market. Results: In total, 42 studies were identified that met the inclusion criteria and were included in the full review. This paper synthesises evidence from 32 studies of individual-oriented interventions; that is, ones based on the strategy of supporting and improving potential employees (as distinct from ones that aim to improve the employment environment). These covered the three major national initiatives: the One Advisory Service, New Deal for Disabled People, and Pathways to Work, and initiatives packaged with them (eg, Return to Work Credit, Permitted Work Rules, Condition Management Programme) . There was evidence that personal advisors and individual case management in these schemes helped some participants back to work. However, these results were biased by widespread selection into these programmes of more work-ready claimants. Qualitative studies revealed the time pressures and requirements to fill job outcome targets that influenced the advisors' selection of claimants. Claimants were concerned about reduction in income and benefit sanctions that advisors could impose. This worked against the building up of mutual trust needed for the individual case management to work effectively. Conclusions: Selection into these programmes of more work ready claimants creates difficulties in judging to what extent the employment effects reported in the quantitative studies derive from the programmes or from the motivations of the individuals. We consider the implications for recent and future UK reforms of the finding that those furthest from the labour market need long-term engagement based on mutual trust to help them move towards work.